Effects of sprint interval training compared to high intensity interval training on repeated sprint capacity and sport-specific performance in college-aged male tennis players - Jing Fan; Ke Sun; Xu Liu; Tianyu Zhu; Yue Li (PLoS ONE, 2025)
Purpose This study compared the effects of sprint interval training (SIT) versus high-intensity interval training (HIIT) on repeated sprint capacity and sport-specific performance in male tennis players. Methods Thirty collegiate tennis players (age: 22.39 ± 1.64 years) were randomly assigned to SIT (n = 15) or HIIT (n = 15) groups for an 8-week training intervention. Performance and physiological parameters were assessed using repeated sprint ability (RSA) test, hit-and-turn tennis test, and tennis-specific endurance test. Key metrics included maximal completed level, total time to exhaustion (TTE), repeated sprint parameters (RSATT, RSAbest, Sdec), maximal oxygen uptake (V˙O₂max), ventilatory efficiency, and tennis performance index. Results Significant group × time interactions were observed for maximal completed level (F(1, 28)=22.649, p < 0.001, ηp2 = 0.89), RSATT (F(1, 28) =39.74, p < 0.001, ηp2 = 0.89), and ball accuracy (F(1, 28)=13.811, p < 0.001, ηp2 = 0.901). The SIT group showed greater improvements in maximal completed level (4.00 ± 0.28 vs. 2.14 ± 0.28, p < .001), RSATT (−4.84 ± 0.33s vs. −1.87 ± 0.33s, p < 0.001), and ball accuracy (12.85 ± 1.71% vs. 3.86 ± 1.71%, p < 0.001). Both groups improved significantly in V˙O₂max (SIT: 52.84 ± 4.22 to 64.50 ± 3.85 mL.min-1.kg-1; HIIT: 51.79 ± 5.15 to 59.6 ± 4.44 mL.min-1.kg-1, p < 0.001) and TTE (SIT: ηp2 = 0.825; HIIT: ηp2 = 0.59). Time to the onset of blood lactate accumulation (OBLA) and second ventilatory threshold (VT2) showed significant main effects of time (p < .001) without group differences. Conclusion While both protocols improved aerobic fitness, SIT demonstrated superior effectiveness in enhancing tennis-specific performance, particularly in repeated sprint ability and technical stability. These findings suggest that SIT might be a more time-efficient training strategy for improving sport-specific performance in tennis players.